Patient reported experiences and readmissions for people with diabetes-related foot disease admitted to public hospitals, New South Wales, Australia, 2019-2022. - Alexander C R Burnett; Jennifer Williamson; Aedan G K Roberts; Sadaf Marashi-Pour; Liz Hay (PLoS ONE)
Objective Patient reported measures of hospital care are known predictors of readmission, even after accounting for risk related to age and comorbidities. This study aimed to determine the association between patient experience of diabetes-related foot disease (DFD) hospital care and unplanned hospital readmission, with a primary focus on DFD-related readmissions and a secondary focus on all-cause readmissions. Methods A retrospective longitudinal cohort study was conducted by linking NSW Adult Admitted Patient Survey data with administrative hospital data for persons hospitalised with DFD identified through diagnostic and/or procedure codes. Univariable and multivariable shared-frailty Cox regression models were used to examine the association between key aspects of patient experiences and 90-days unplanned hospital readmission over the period 2019-2022. Results Overall, 3,173 DFD patients were included. Ninety-day readmission rates for respondents with DFD were 9% for DFD-related readmissions and 16% for all-cause readmissions. Adults with DFD who could not understand explanations offered by health professionals were at increased risk of DFD-related readmission compared to those who could always understand (Hazard ratio (HR) 2.43, CI: 1.47-4.00), as well as patients who did not feel well enough to leave hospital at discharge (HR 1.93, CI: 1.41-2.64) or reported the care received was not well organised (HR 2.24, 1.45-3.47). Patients reporting that they did not receive enough information regarding their condition, treatment, or how to manage care at home were found to have a DFD-related readmission risk that was 1.5 to 1.8-times greater than those who did. Similar patterns were observed for all-cause readmissions, albeit with generally smaller effect sizes. Conclusions The findings highlight that elements of care related to communication, coordination, and involvement in decision making may influence unplanned readmission rates for patients with chronic conditions, such as DFD. The impact appears to be more pronounced for DFD-related readmissions compared to all-cause readmissions.